A virtual library - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
OSSREA on CD Research Publications and Official Documents OSSREA, version 1, 2001. CD-ROM cased. GBP 12.95 Euro 19.85